Synchronization method based on a new constant envelop preamble for OFDM systems - Ren, G.; Chang, Y.; Zhang, H. (IEEE transactions on broadcasting, 2005)
The synchronization method using the available constant envelop preamble is analyzed, and a new preamble weighted by pseudo-noise sequence is proposed, with which a novel timing and frequency offset estimation method is presented for orthogonal frequency division multiplexing (OFDM) systems in this paper. By the proposed method, the accuracy of the timing offset estimator is significantly improved, and the estimate range of the frequency offset estimator is greatly enlarged with no loss in accuracy. The performance of the proposed method is demonstrated by simulations.